2015
DOI: 10.1021/acs.inorgchem.5b00269
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Peroxo-Precursor Synthesis Method and Structure Evolution of Large Specific Surface Area Mesoporous BaSnO3

Abstract: In this paper, we propose a facile and efficient strategy for synthesizing mesoporous BaSnO3 with a surface area as large as 67 m(2)/g using a peroxo-precursor decomposition procedure. As far as we know, this is the largest surface area reported in literature for BaSnO3 materials and may have a potential to greatly promote the technological applications of this kind of functional material in the area of chemical sensors, NOx storage, and dye-sensitized solar cells. The structure evolution of the mesoporous BaS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 55 publications
3
40
2
Order By: Relevance
“…In order to investigate the crystallization mechanism, the formation process of layered In(OH) 3 was studied. To the best of our knowledge, Sn 4+ is normally coordinated with OOH − to form precipitates in a hydrogen peroxide (H 2 O 2 ) aqueous solution under basic conditions . Since In 3+ and Sn 4+ have the same electronic configuration, namely 4d 10 , it seems that In 3+ ions also have a strong tendency to be coordinated by OOH − to form precipitates under basic conditions, which was validated by the following experiments.…”
Section: Figuresupporting
confidence: 55%
See 1 more Smart Citation
“…In order to investigate the crystallization mechanism, the formation process of layered In(OH) 3 was studied. To the best of our knowledge, Sn 4+ is normally coordinated with OOH − to form precipitates in a hydrogen peroxide (H 2 O 2 ) aqueous solution under basic conditions . Since In 3+ and Sn 4+ have the same electronic configuration, namely 4d 10 , it seems that In 3+ ions also have a strong tendency to be coordinated by OOH − to form precipitates under basic conditions, which was validated by the following experiments.…”
Section: Figuresupporting
confidence: 55%
“…To the best of our knowledge, Sn 4 + is normally coordinated with OOH À to form precipitates in ah ydrogen peroxide (H 2 O 2 )a queous solution under basic conditions. [26][27][28] SinceI n 3 + andS n 4 + have the same electronic configuration, namely 4d 10 ,i ts eems that In 3 + ions also have as trong tendency to be coordinated by OOH À to form precipitates under basic conditions, whichw as validated by the following experiments. The0 .1 m indium nitrate hydrogen peroxide aqueouss olution( 30 %H 2 O 2 )w as added into concentrated ammonia water,a nd then formed precipitates with the helpo fS r 2 + .N ote that replacing Sr 2 + by Ca 2 + can also lead to precipitates whichc an then be transformedi nto layered In(OH) 3 ,b ut almost no precipitates were obtained in the similar conditions without the helpo fb ivalent cations.…”
mentioning
confidence: 99%
“…5) could be well fitted by a single Lorentzian curve, indicating that Sn cations in these catalysts retained homogeneous and unique state. The IS values observed for all these samples lied in the range from 0.00 to 0.08 mm/s, which was characteristic of Sn 4+ species (4d 10 5s 0 5p 0 , IS = -0.4  2.0 mm/s) [59,60] . This result confirmed that Sn ions were exclusively in the +4 oxidation state.…”
Section: Catalytic Performance For N 2 O Decompositionmentioning
confidence: 82%
“…图 10 纯的和Al掺杂的TiO 2 纳米颗粒1.9~10 K低温摩尔比 热(C/T-T图) [45] (网络版彩图) [52] (网络版彩图) (网络版彩图) Figure 13 Plot of the experimental heat capacities of BS-T (T=400, 500, 600, and 800) samples measured over the temperature range from 2 to 300 K. Insets show the data below T=10 K [59] (color online).…”
Section: Figurementioning
confidence: 99%